Otherness, memory and racism in Augusto Higa’s Okinawa existe - Gilbonio Navarro, Oscar Abraham (2025)
Peru registers various immigrations where the foreigner, due to his language, culture, phenotype and other distinctive features, represents an otherness exposed to varied feelings and setbacks. Augusto Higa investigates the memory of his Japanese ancestors in their first adventures on Peruvian soil around the Second World War. With readings by Tzvetan Todorov we address otherness, collective memory, human diversity and the meeting of cultures in three stories from the book Okinawa Exists. The first and namesake configures the migrant’s longing for his homeland and his desire to keep his reference intact. “Foreign” shows that within a community there may be unforeseen aversion factors. “Dust in love” constitutes the metaphor of the possible love between beings from different communities prevented by ethnocentric criteria. Higa also shows frescoes of a host society with profound racist atavism and events not sufficiently exposed in official history.